PEMODELAN KURVA IMBAL HASIL DAN KOMPUTASINYA DENGAN PAKET SOFTWARE RCMDRPLUGIN.ECONOMETRICS - Rosadi, Dedi (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2011)
In this paper discussed the yield curve modeling methodology using the Nelson-Siegel model Svenson (Svensson, 1994) with special application to model the Indonesian Government Securities Yield Curve. The focus of this study is the computation of the yield curve model using the R, especially using a tool called the R-GUI RcmdrPlugin.Econometrics (Rosadi, 2011). For the empirical illustration, also given examples of applications using real data from the Indonesian capital market. Â Keywords: Kurva yield, R-GUI, Nelson-Siegel-Svenson